ANALISIS PENERAPAN PENCATATAN LAPORAN KEUANGAN SEDERHANA PADA UMKM CHIA OLSHOP DI KOTA JAKARTA SELATAN BERDASARKAN SAK EMKM UMKM CHIA OLSHOP - Fauziah, Dini Saidah; Surbakti, Sevani Relitna Br; Pane, Citra Swantika; Rahmadi, Zara Tania (ASOSIASI IDEBAHASA KEPRI, 2025)
This study aims to analyze the application of simple financial report recording at UMKM Chia Olshop in South Jakarta based on the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM). The research employs a qualitative descriptive approach using a case study methodology. Data collection was conducted through interviews, observations, and document analysis. The findings indicate that Chia Olshop still uses a very basic financial recording system, focusing only on sales transactions without proper documentation of operational costs and purchases. The application of SAK EMKM provides a structured and systematic approach to financial reporting, helping the business to better understand its financial performance. The study recommends that Chia Olshop adopt SAK EMKM fully to enhance financial transparency and support future business growth.